Evaluation of a flowchart-based EHR query system: A case study of RetroGuide - Huser, Vojtech; Narus, Scott P.; Rocha, Roberto A. (Journal of biomedical informatics, 2010)
Provision of query systems which are intuitive for non-experts has been recognized as an important informatics challenge. We developed a prototype of a flowchart-based analytical framework called RetroGuide that enables non-experts to formulate query tasks using a step-based, patient-centered paradigm inspired by workflow technology. We present results of the evaluation of RetroGuide in comparison to Structured Query Language (SQL) in laboratory settings using a mixed method design. We asked 18 human subjects with limited database experience to solve query tasks in RetroGuide and SQL, and quantitatively compared their test scores. A follow-up questionnaire was designed to compare both technologies qualitatively and investigate RetroGuide technology acceptance. The quantitative comparison of test scores showed that the study subjects achieved significantly higher scores using the RetroGuide technology. Qualitative study results indicated that 94% of subjects preferred RetroGuide to SQL because RetroGuide was easier to learn, it better supported temporal tasks, and it seemed to be a more logical modeling paradigm. Additional qualitative evaluation results, based on a technology acceptance model, suggested that a fully developed RetroGuide-like technology would be well accepted by users. Our study is an example of a structure validation study of a prototype query system, results of which provided significant guidance in further development of a novel query paradigm for EHR data. We discuss the strengths and weakness of our study design and results, and their implication for future evaluations of query systems in general.